2011
DOI: 10.1099/mic.0.040451-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a non-replicative intracellular stage of nontypable Haemophilus influenzae in epithelial cells

Abstract: Nontypable Haemophilus influenzae (NTHi) is a Gram-negative, non-capsulated human bacterial pathogen, a major cause of a repertoire of respiratory infections, and intimately associated with persistent lung bacterial colonization in patients suffering from chronic obstructive pulmonary disease (COPD). Despite its medical relevance, relatively little is known about its mechanisms of pathogenicity. In this study, we found that NTHi invades the airway epithelium by a distinct mechanism, requiring microtubule assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
162
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(174 citation statements)
references
References 90 publications
(94 reference statements)
10
162
2
Order By: Relevance
“…In our experiments, we found that activation of the PI3K pathway, which causes FOXO inhibition (26), is capable of enhancing invasion of NTHi in airway epithelial cells as previously described for alveolar epithelial cells (35). Beyond that, we found that silencing of FOXO results in higher intracellular bacterial counts.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…In our experiments, we found that activation of the PI3K pathway, which causes FOXO inhibition (26), is capable of enhancing invasion of NTHi in airway epithelial cells as previously described for alveolar epithelial cells (35). Beyond that, we found that silencing of FOXO results in higher intracellular bacterial counts.…”
Section: Discussionsupporting
confidence: 85%
“…Another approach that we used to evaluate FOXO innate immune functions was an NTHi uptake assay, a common method to detect intracellular bacteria (35,40). In our experiments, we found that activation of the PI3K pathway, which causes FOXO inhibition (26), is capable of enhancing invasion of NTHi in airway epithelial cells as previously described for alveolar epithelial cells (35).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations